Carrier for analysis, manufacturing method for carrier for analysis, and analyzing method

The development of an analytical carrier with a porous aluminum structure and controlled organic acid concentration addresses autofluorescence issues in nitrocellulose membrane filters, improving sensitivity and signal-to-noise ratio in fluorescence measurements.

JP2024178628APending Publication Date: 2024-12-25NIPPON LIGHT METAL CO LTD +1

Patent Information

Application Number
JP2023096908
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-25

AI Technical Summary

Technical Problem

Nitrocellulose membrane filters used in immunochromatography emit high autofluorescence, which interferes with fluorescence measurement, reducing sensitivity and signal-to-noise ratio in analytical methods.

Method used

An analytical carrier composed of a metal member with a porous body formed by aggregated aluminum particles and an anodic oxide film, having a porosity of 30% by volume or more, an average particle diameter of 0.1 μm to 20 μm, and an organic acid concentration of 150 mg/m²/100μm or less, is developed to suppress autofluorescence.

Benefits of technology

The analytical carrier effectively reduces autofluorescence, enhancing sensitivity and signal-to-noise ratio in fluorescence measurements by minimizing background noise and improving signal detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178628000001_ABST
    Figure 2024178628000001_ABST
Patent Text Reader

Abstract

To provide a carrier for analysis that can suppress self-fluorescence.SOLUTION: A carrier 1 for analysis comprises a metal member 10 including a porous body 20, which includes a skeleton 22 formed by gathering a plurality of aluminum particles 21, and a plurality of gaps 23 encircled with the skeleton 22. The skeleton 22 has an outer shell 24, including an anodic oxide film including aluminum oxide, on surfaces of aluminum particles 21, wherein the porous body 20 has a porosity of 30 vol.% or more, the plurality of aluminum particles 21 have an average particle size of 0.1 to 20 μm, and the metal member 10 has an organic acid concentration of 150 / m2 / 100 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an analytical support, a method for producing an analytical support, and an analytical method. [Background technology]

[0002] Immunochromatography is known as one type of analytical method for analyzing an analyte supported on an analytical carrier (see Patent Document 1). A lateral flow type test kit using immunochromatography is also known. This test kit includes a test strip in which a capture antibody that reacts with the analyte is fixed to a predetermined site on the analytical carrier.

[0003] In this test kit, for example, a specimen containing an antigen to be analyzed is collected from a living body, and a solution containing the specimen is dropped at a predetermined position on a test strip. The antigen then reacts with a labeled antibody labeled with particles such as gold colloid particles and latex particles to form a complex. The solution containing the complex then flows through the analytical carrier by capillary action. Furthermore, when the solution containing the complex is developed by the analytical carrier, the antigen contained in the complex is captured by the capture antibody on the analytical carrier, and the complex gathers at the capture site, causing color development. In this way, the degree of color development occurring at the capture site in a state in which the complex is supported by the analytical carrier is confirmed with the naked eye, thereby determining whether the antigen is contained in the specimen. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-344406 A Summary of the Invention [Problem to be solved by the invention]

[0005] In Patent Document 1, a nitrocellulose membrane filter is used as an analytical carrier. Nitrocellulose membrane filters generally have a high whiteness, making it relatively easy to visually confirm the test line and control line, and have excellent development performance due to capillary action. For this reason, they are used in many test kits.

[0006] On the other hand, fluorescence measurement is performed as a type of analysis method using immunochromatography. In fluorescence measurement, for example, an analyte is reacted with an antibody labeled with fluorescent beads to form a complex, and the complex is reacted with a capture antibody fixed to an analytical carrier. Then, the analytical carrier carrying the analyte is irradiated with excitation light of a specific wavelength, and the fluorescence emitted from the fluorescent beads is detected, thereby performing a fluorescence analysis of the analyte. In this case, the fluorescence emitted from the fluorescent beads bound to the capture antibody and the analyte becomes a signal, and the fluorescence emitted from other sources becomes noise. However, when a nitrocellulose membrane filter is used as an analytical carrier, it itself emits high autofluorescence, which is an obstacle to achieving high sensitivity.

[0007] The present disclosure has been made in consideration of the problems inherent in the conventional techniques, and an object of the present disclosure is to provide an analytical carrier capable of suppressing autofluorescence, a method for producing the analytical carrier, and an analytical method using the analytical carrier. [Means for solving the problem]

[0008] The analytical support according to the first aspect of the present disclosure is an analytical support including a metal member containing a porous body. The porous body includes a skeleton formed by an assembly of a plurality of aluminum particles, and a plurality of voids surrounded by the skeleton. The skeleton has an outer shell including an anodized film containing aluminum oxide on the surface of the aluminum particle. The porosity of the porous body is 30 volume % or more. The average particle diameter of the plurality of aluminum particles is 0.1 μm to 20 μm. The organic acid concentration of the metal member is 150 mg / m 2 / 100μm or less.

[0009] A method for producing an analytical support according to a second aspect of the present disclosure is a method for producing an analytical support comprising a metal member including a porous body. The porous body includes a skeleton formed by an assembly of a plurality of aluminum particles, and a plurality of voids surrounded by the skeleton. The skeleton has an outer shell including an anodized film including aluminum oxide on the surface of the aluminum particles. The production method includes a sintering step of sintering a plurality of aluminum metal particles to obtain a sintered body, and an anodizing step of anodizing the sintered body to form an outer shell including an anodized film on the surface of the aluminum metal particles. The average particle diameter of the plurality of aluminum metal particles is 0.1 μm to 20 μm. The packing rate of the sintered body is 20 vol % to 70 vol %. The organic acid concentration of the metal member is 150 mg / m 2 / 100μm or less.

[0010] An analytical method according to a third aspect of the present disclosure is an analytical method for analyzing an analyte supported on an analytical support. The analytical support is an analytical support comprising a metal member including a porous body. The porous body includes a skeleton formed by an assembly of a plurality of aluminum particles, and a plurality of voids surrounded by the skeleton. The skeleton has an outer shell including an anodized film containing aluminum oxide on the surface of the aluminum particle. The porosity of the porous body is 30 volume % or more. The average particle diameter of the plurality of aluminum particles is 0.1 μm to 20 μm. The organic acid concentration of the metal member is 150 mg / m 2 The analysis method includes an irradiation step of irradiating the analytical support carrying the analyte with light having at least one wavelength included in the ultraviolet region to the infrared region, and a detection step of detecting at least one type of light selected from the group consisting of reflected light, scattered light, transmitted light, fluorescence, and phosphorescence of the irradiated light. Effect of the Invention

[0011] According to the present disclosure, it is possible to provide an analytical carrier capable of suppressing autofluorescence, a method for producing the analytical carrier, and an analytical method using the analytical carrier. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an enlarged structure of a part of a porous body of an analytical support according to one embodiment. [Diagram 2] FIG. 2 is a cross-sectional view illustrating an example of a metal member according to an embodiment. [Diagram 3] FIG. 1 is a perspective view showing an example of a test strip using an analytical carrier according to one embodiment. [Figure 4] 1 shows scanning images of test strips for measuring autofluorescence according to Example 3 and Reference Example 1 at an excitation wavelength of 488 nm. [Diagram 5] 1 shows scanning images of test strips for measuring autofluorescence according to Example 3 and Reference Example 1 at an excitation wavelength of 532 nm. [Figure 6] 1 shows scanning images of test strips on which antibodies according to Example 3 and Reference Example 1 are immobilized at an excitation wavelength of 488 nm. [Figure 7] 1 shows scanning images of test strips on which antibodies according to Example 3 and Reference Example 1 are immobilized at an excitation wavelength of 532 nm. [Figure 8] 1 is a graph showing the relationship between the total organic acid concentration and the autofluorescence intensity. [Figure 9] 1 is a graph showing the relationship between total inorganic acid concentration and autofluorescence intensity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The analytical carrier, the manufacturing method of the analytical carrier, and the analytical method according to the present embodiment will be described in detail below with reference to the drawings. The present disclosure is not limited to the following embodiments. In addition, the components in the embodiments can be combined in part or in whole as appropriate. Note that the dimensional ratios in the drawings are exaggerated for the convenience of explanation and may differ from the actual ratios.

[0014] [1. Analytical Carriers] First, the analytical carrier according to this embodiment will be described. Conventionally, when a nitrocellulose membrane filter is used as an analytical carrier, it generates high autofluorescence, which is an obstacle to achieving high sensitivity. Therefore, in the analytical carrier according to this embodiment, the organic acid concentration of the metal member is reduced. As will be described in detail later, it has been found that the analytical carrier according to this embodiment can suppress the autofluorescence of the analytical carrier by reducing the organic acid concentration. Note that autofluorescence is also called autofluorescence or primary fluorescence, and refers to fluorescence generated by the inherent characteristics of the analytical carrier.

[0015] <Porous body> FIG. 1 is a schematic cross-sectional view showing a partially enlarged structure of a porous body 20 of an analytical carrier 1. As shown in FIG. 1, the analytical carrier 1 includes a metal member 10, and the metal member 10 includes a porous body 20. The porous body 20 includes a plurality of aluminum particles 21. Furthermore, the porous body 20 includes a plurality of voids 23. More specifically, the porous body 20 includes a skeleton 22 formed by an assembly of a plurality of aluminum particles 21, and the voids 23 surrounded by the skeleton 22. The skeleton 22 includes an outer shell 24, and the surface of the skeleton 22 is formed by the outer shell 24. In the porous body 20, the plurality of aluminum particles 21 are connected via the outer shell 24 to form a skeleton 22 with a three-dimensional network structure, and the outer shell 24 is disposed on the outer surface side of the analytical carrier 1.

[0016] In this way, the porous body 20 is a porous body having voids 23 inside that communicate with the outside. At this time, the voids 23 are surrounded by the outer shell 24. That is, the voids 23 are formed surrounded by the skeleton 22 inside the porous body 20 or the outer shell 24 formed on its surface. The voids 23 forming one cell structure surrounded by the outer shell 24 may be connected to the voids 23 forming another cell structure. Specifically, the porous body 20 may have an open cell structure. In addition, the single void 23 or the multiple voids 23 may or may not penetrate from one surface of the porous body 20 to the other surface.

[0017] The analytical carrier 1 includes a porous body 20. The porous body 20 is obtained by sintering an aluminum powder containing a plurality of aluminum particles 21, or a compact obtained by compacting the aluminum powder, to obtain a sintered body, and then subjecting the sintered body to an anodizing process described below. The porous body 20 includes a skeleton 22 formed by an assembly of the plurality of aluminum particles 21. The porous body 20 also includes voids 23 surrounded by the skeleton 22. The skeleton 22 has an outer shell 24 on the surface of the aluminum particles 21.

[0018] Here, in immunochromatography, as described later, a label such as fluorescent beads is used. When the analytical carrier 1 is used, for example, in an immunochromatographic test strip, the porous body 20 can suck up the solution in which the label is dispersed by capillary action. The mechanism of this is presumed to be that the solution in which the label is dispersed penetrates into the space of the voids 23 present inside the porous body 20, and a part of it travels along the surface of the porous body 20.

[0019] The aluminum particles 21 have an average particle diameter of 0.1 μm to 20 μm. By setting the average particle diameter to 0.1 μm or more, the strength of the porous body 20 is improved, and damage during transportation or the like can be suppressed. By setting the average particle diameter to 20 μm or less, the flow rate of the analytical carrier 1 can be improved. The average particle diameter may be 1 μm or more, 3 μm or more, or 5 μm or more. The average particle diameter may be 18 μm or less, 15 μm or less, or 10 μm or less.

[0020] The average particle diameter of the plurality of aluminum particles 21 can be measured by observing the cross section of the porous body 20 with a scanning electron microscope. For example, the aluminum particles 21 after sintering are in a state where some of them are melted and connected, but the portion having a substantially circular shape can be approximately regarded as being circular. Therefore, in the above-mentioned cross-sectional observation, the maximum diameter (long diameter) of each of the aluminum particles 21 having a substantially circular shape is taken as the particle diameter, and the particle diameters of 50 arbitrary aluminum particles 21 are measured, and the arithmetic average of these is taken as the average particle diameter of the aluminum particles 21 after sintering. The average particle diameter of the plurality of aluminum metal particles before sintering is the D50 value obtained by measuring the particle size distribution on a volume basis by a laser diffraction method. Note that if it is within the range of 0.1 μm to 20 μm, almost no secondary particles are formed. Therefore, the average particle diameter of the aluminum particles 21 after sintering observed with a scanning electron microscope is almost the same as the average particle diameter of the aluminum metal particles before sintering measured by a laser diffraction method.

[0021] The shape of each aluminum particle 21 is not particularly limited, and may be spherical, polygonal, irregular, scaly, or fibrous. Among these, it is preferable that each aluminum particle 21 contained in the plurality of aluminum particles is spherical. When each aluminum particle 21 is spherical, the size of the plurality of voids 23 is uniform. For example, in immunochromatography, as described later, a label such as a fluorescent bead is used. If the size of the voids 23 is uniform, such a label is not captured in the voids 23 and can flow smoothly through the porous body 20. The spherical shape referred to here may not only be a perfect sphere, but may also be one having a slight unevenness on the surface. The spherical shape referred to here may include not only one having an aspect ratio of 1, but also one having an aspect ratio of 5 or less, 3 or less, or 2 or less. The aspect ratio is the ratio of the major axis to the minor axis of the aluminum particle 21, and is the average value of the plurality of aluminum particles 21.

[0022] The average pore size of the porous body 20 is preferably 2.5 μm to 20 μm. By setting the average pore size to 2.5 μm or more, the water wicking performance of the analytical carrier 1 can be improved. Here, the particle size of typical fluorescent beads used in immunochromatography is about 10 nm to 50 nm, and there are also labels with larger particle sizes. When the analytical carrier 1 is used, for example, in an immunochromatographic test strip, by setting the average pore size to 2.5 μm or more, such labels are not captured in the voids 23 and can flow smoothly through the porous body 20. In addition, by setting the average pore size to 20 μm or less, the water wicking performance of the analytical carrier 1 can be improved. The average pore size may be 3 μm or more, or may be 4 μm or more. In addition, the average pore size may be 15 μm or less, or may be 10 μm or less. The average pore size can be measured by mercury intrusion porosimetry. In this specification, the average pore size refers to the volume-based median size.

[0023] The porosity of the porous body 20 is 30% by volume or more. The porosity of the porous body 20 may be 30% by volume to 99% by volume. By setting the porosity of the porous body 20 to 30% by volume or more, the water suction performance can be improved. By setting the porosity to 99% by volume or less, peeling of the aluminum particles 21 from the porous body 20 can be suppressed, and the strength of the porous body 20 can be improved. The porosity may be 40% by volume or more, 50% by volume or more, 60% by volume or more, 70% by volume or more, 80% by volume or more, 90% by volume or more, or 92% by volume or more. The porosity may be 95% by volume or less, or 93% by volume or less. The porosity is the ratio of the volume of the pores in the porous body 20 to the total volume of the porous body 20. The porosity can be obtained by dividing the pore volume occupied by the voids 23 contained in the porous body 20 portion, which is obtained by submerging the analytical carrier in water and evacuating it, by the apparent volume of the porous body 20 portion, as described in the Examples section below.

[0024] The thickness of the porous body 20 is preferably 20 μm to 10 cm. By making the thickness of the porous body 20 20 μm or more, it is easy to ensure a sufficient thickness for absorbing water by capillary action. By making the thickness of the porous body 20 10 cm or less, it is possible to prevent the porous body 20 from cracking even when it is wound up on a roll for transportation or the like. The thickness of the porous body 20 is preferably 30 μm or more, more preferably 40 μm or more, and even more preferably 50 μm or more. The thickness of the porous body 20 is more preferably 1000 μm or less, even more preferably 200 μm or less, and particularly preferably 150 μm or less.

[0025] The porous body 20 may be composed of a single porous layer, but may include multiple porous layers. The porous body 20 may include, for example, a first porous layer and a second porous layer disposed on the surface of the first porous layer. The first porous layer and the second porous layer may differ from each other in the average particle size, aspect ratio, or constituent material of the multiple aluminum particles 21, the porosity of the porous body 20, or the average pore size. For example, the average particle size of each aluminum particle 21 contained in the first porous layer may be larger than the average particle size of each aluminum particle 21 contained in the second porous layer. The thicknesses of the first porous layer and the second porous layer may be the same or different.

[0026] <Outer shell> The outer shell 24 includes an anodized film containing aluminum oxide. The anodized film contained in the outer shell 24 may be a barrier-type anodized film or a porous-type anodized film. The outer shell 24 may have only a barrier-type anodized film formed on the surface of the aluminum particle 21, or may have a two-layer structure in which a barrier-type anodized film is formed on the surface of the aluminum particle 21 and a porous-type anodized film is further formed on the outside. The outer shell 24 may have a hydrated film containing aluminum hydroxide. The hydrated film is formed in a hydration treatment process described later.

[0027] The outer shell 24 preferably has a thickness of 0.1 nm to 1000 nm. By setting the thickness of the outer shell 24 in such a range, it is possible to provide an analytical carrier 1 having sufficiently high corrosion resistance. The thickness of the outer shell 24 may be 1 nm or more, or 10 nm or more. The thickness of the outer shell 24 may be 200 nm or less, or 100 nm or less. The thickness of the outer shell 24 can be measured, for example, by observing a cross section of the outer shell 24 with a scanning electron microscope or the like.

[0028] <Metal parts> As shown in FIG. 2, the metal member 10 may further include a substrate 50. That is, the metal member 10 may include only the porous body 20 and, optionally, the substrate 50. The metal member 10 may include only the porous body 20 and the substrate 50. The metal member 10 may include only the porous body 20. The substrate 50 can support the porous body 20 and can improve the rigidity of the analytical support 1. The substrate 50 may have a layered or plate-like shape.

[0029] The porous body 20 may be provided on at least one surface of the substrate 50. Specifically, the porous body 20 may be provided on only one surface of the substrate 50, or on both surfaces of the substrate 50. The porous body 20 is preferably disposed on the outermost surface of the analytical support 1.

[0030] The analytical carrier 1 does not necessarily have to include the substrate 50, and therefore the thickness of the substrate 50 is greater than 0 μm. The thickness of the substrate 50 depends on the application, and may be, for example, 1 mm or less, 100 μm or less, 10 μm or less, or 1 μm or less.

[0031] The base material 50 may be made of the same material as the aluminum particles 21. Specifically, the base material 50 may contain at least one of aluminum and an aluminum alloy. That is, the metal member 10 may be an aluminum member. The material constituting the base material 50 may be the same as the material constituting the aluminum particles 21, or may be different.

[0032] The thickness of the metal member 10 may be, for example, 20 μm or more and 10 cm or less, depending on the application. By setting the thickness of the metal member 10 in such a range, it is possible to provide an analytical carrier 1 having good bending strength. The thickness of the metal member 10 may be 30 μm or more, 50 μm or more, 100 μm or more, or 150 μm or more. The thickness of the metal member 10 may be 1000 μm or less, 300 μm or less, or 200 μm or less.

[0033] The organic acid concentration of the metal member 10 is 150 mg / m 2 / 100 μm or less. By setting the organic acid concentration of the metal member 10 to the above value or less, the generation of autofluorescence from the porous body 20 can be suppressed. Furthermore, by setting the organic acid concentration of the metal member 10 to the above value or less, when the analytical carrier 1 after a flow test in which a solution containing an analyte is flowed through the analytical carrier 1 is subjected to fluorescence measurement, the background signal intensity and noise value emitted from areas other than the spot where the analyte is detected can be reduced. In this way, according to the analytical carrier 1, when an analysis is performed in which excitation light is irradiated onto the analytical carrier 1 and the emitted light is detected, the signal from the spot derived from the analyte can be easily detected with high sensitivity.

[0034] Although the analytical carrier 1 according to this embodiment is not limited to the following mechanism, it is presumed that the autofluorescence was suppressed by reducing the organic acid concentration because the anodized film of the porous body 20 contained a small number of conjugated systems. In general, the presence of conjugated systems such as double bonds and benzene rings causes fluorescence from the conjugated systems. As described later, the anodized film is produced by anodizing in an electrolyte, and the components contained in the electrolyte during anodizing are incorporated into the anodized film. Here, since the organic acid itself does not emit fluorescence, it is considered that when the electrolyte contains an organic acid, the organic acid contained in the electrolyte is oxidized, etc., to generate organic acid-derived substances containing conjugated systems. That is, when anodization is performed in an electrolyte containing an organic acid, it is considered that organic acid-derived substances are generated from the organic acid incorporated into the anodized film, or organic acid-derived substances generated in the electrolyte are incorporated into the anodized film, causing the porous body 20 to contain organic acid-derived substances. It is believed that when the organic acid concentration measured from the metal member 10 is high, the autofluorescence increases due to an increase in the fluorescence generated from the conjugated system of the organic acid-derived substance contained in the porous body 20. In addition, when anodization is performed in an electrolyte containing an organic acid and the anodized film becomes thick, the autofluorescence increases due to the incorporation of a large amount of organic acid or organic acid-derived substance into the anodized film.

[0035] The organic acid concentration is the total content of organic acids in an extract obtained by extracting the metal member 10 of the analytical carrier 1 with a liquid containing water, as described in the Examples section below. 2 The organic acid concentration means the content of organic acid per unit weight. The organic acid concentration can be calculated by ion analysis using the extract. The ion analysis can be performed by ion chromatography and ICP emission spectrometry as described in the Examples section below.

[0036] The anodized film may be an organic acid anodized film or an inorganic acid anodized film. The organic acid anodized film suppresses the denaturation of proteins such as antibodies bound to the analytical carrier 1, and therefore can suppress the decrease in signal intensity from labels such as fluorescent substances. This can improve the S / N ratio. The organic acid anodized film refers to an anodized film in which the concentration of organic acid eluted from the anodized film is higher than the concentration of inorganic acid. The organic acid anodized film may have an organic acid concentration of 60% or more, 70% or more, 80% or more, or 90% or more of the total of the organic acid concentration and the inorganic acid concentration. The inorganic acid anodized film refers to an anodized film in which the concentration of inorganic acid eluted from the anodized film is higher than the concentration of organic acid. The inorganic acid anodized film may have an inorganic acid concentration of 60% or more, 70% or more, 80% or more, or 90% or more of the total of the organic acid concentration and the inorganic acid concentration. The organic acid anodized film may be formed by anodizing with an electrolytic solution containing an organic acid. The inorganic acid anodized film may be formed by anodizing with an electrolytic solution containing an inorganic acid. The organic acid concentration may be measured by the above-mentioned method, and the inorganic acid concentration may be measured by the same method. Anodization will be described later.

[0037] The anodized film may be at least one selected from the group consisting of a citric acid anodized film, an adipic acid anodized film, and an oxalic acid anodized film. Such organic acid anodized films are less likely to cause denaturation of proteins such as antibodies bound to the analytical carrier 1, and therefore can suppress a decrease in signal intensity from labels such as fluorescent substances. Therefore, the SN ratio can be improved. The citric acid anodized film refers to an anodized film in which the organic acid with the highest concentration of the organic acid eluted from the anodized film is citric acid. The adipic acid anodized film refers to an anodized film in which the organic acid with the highest concentration of the organic acid eluted from the anodized film is adipic acid. The oxalic acid anodized film refers to an anodized film in which the organic acid with the highest concentration of the organic acid eluted from the anodized film is oxalic acid. The organic acid concentrations can be measured by ion analysis in the same manner as described above.

[0038] The anodized film may be at least one selected from the group consisting of a sulfuric acid anodized film, a phosphoric acid anodized film, and a boric acid anodized film. Such inorganic acid anodized films have a low organic acid concentration in the metal member 10. Therefore, the generation of autofluorescence from the analytical carrier 1 is suppressed, and the background signal intensity and noise value after the flow test can be reduced. The sulfuric acid anodized film refers to an anodized film in which the inorganic acid with the highest concentration is sulfuric acid among the inorganic acids eluted from the anodized film. The phosphoric acid anodized film refers to an anodized film in which the inorganic acid with the highest concentration is phosphoric acid among the inorganic acids eluted from the anodized film. The boric acid anodized film refers to an anodized film in which the inorganic acid with the highest concentration is boric acid among the inorganic acids eluted from the anodized film. These inorganic acid concentrations can be measured by ion analysis in the same manner as the above-mentioned method.

[0039] The anodized film may be at least one selected from the group consisting of a citric acid anodized film, an adipic acid anodized film, an oxalic acid anodized film, a phosphoric acid anodized film, and a boric acid anodized film. Such anodized films are less likely to cause denaturation of proteins such as antibodies bound to the analytical carrier 1, and therefore can suppress a decrease in signal intensity from labels such as fluorescent substances. Therefore, the SN ratio can be improved.

[0040] The anodized film may be a weak acid anodized film. Such an anodized film is less likely to cause denaturation of proteins such as antibodies bound to the analytical carrier 1, and therefore can suppress a decrease in signal intensity from labels such as fluorescent substances. This can improve the S / N ratio. The weak acid anodized film refers to an anodized film in which the acid with the highest concentration among the acids eluted from the anodized film is a weak acid. The weak acid anodized film may be at least one selected from the group consisting of a citric acid anodized film, an adipic acid anodized film, an oxalic acid anodized film, a phosphoric acid anodized film, and a boric acid anodized film.

[0041] <Analytical Carrier> As described above, the analytical support 1 according to this embodiment is an analytical support 1 including a metal member 10 including a porous body 20. The porous body 20 includes a skeleton 22 formed by an assembly of a plurality of aluminum particles 21, and a plurality of voids 23 surrounded by the skeleton 22. The skeleton 22 has an outer shell 24 including an anodized film containing aluminum oxide on the surface of the aluminum particle 21. The porosity of the porous body 20 is 30 volume % or more. The average particle diameter of the plurality of aluminum particles 21 is 0.1 μm to 20 μm. The organic acid concentration of the metal member 10 is 150 mg / m 2 / 100μm or less.

[0042] In the analytical carrier 1 according to this embodiment, the organic acid concentration in the metal member 10 is low, so that the autofluorescence emitted from the porous body 20 is suppressed. In addition, the organic acid concentration in the metal member 10 is low, so that the background signal intensity and noise value after the flow test can be reduced. Therefore, according to the analytical carrier 1, it is possible to provide an analytical carrier 1 capable of detecting signals from spots derived from the analyte with high sensitivity.

[0043] The analytical carrier 1 may be an analytical carrier 1 for performing a fluorescence analysis in which fluorescence emitted by irradiating the analytical carrier 1 with excitation light is measured. The analytical carrier 1 according to this embodiment can suppress autofluorescence, and therefore can be suitably used as a carrier for fluorescence analysis.

[0044] The wavelength of the irradiated excitation light may be 250 nm to 650 nm, and the wavelength of the measured fluorescence may be 350 nm to 700 nm. Such excitation wavelengths and fluorescence wavelengths are widely used in general fluorescence analysis, and therefore the analytical carrier 1 according to this embodiment can be widely used.

[0045] The analytical carrier 1 according to this embodiment can analyze the analyte while carrying the analyte. The analytical carrier 1 can suppress autofluorescence and background signal intensity and noise, and can therefore be suitably used as an immunochromatographic test strip. The immunochromatographic test strip is also called an immunochromatographic developing member, a lateral flow assay test strip, or a lateral flow assay developing member. The analytical carrier 1 is also preferably used in in vitro diagnostic drugs such as a test kit using immunochromatography.

[0046] As described above, the analytical carrier 1 can suck up liquid by the capillary action of the porous body 20, and therefore can be used in a lateral flow assay. The flow rate, which indicates the speed at which the analytical carrier 1 sucks up liquid in the longitudinal direction, is not particularly limited, and may be, for example, 1500 seconds or less. In this way, an analytical carrier 1 suitable for, for example, chromatography can be provided. The flow rate may be 1000 seconds or less, 500 seconds or less, 300 seconds or less, 200 seconds or less, or 100 seconds or less. The flow rate can be obtained by immersing the analytical carrier 1 in pure water at room temperature (30° C.) so that the planar direction of the analytical carrier 1 is perpendicular to the liquid surface, and measuring the time required to suck up water to a height of 4 cm by capillary action. The pure water is pure water with a resistivity of 10 kΩm measured at 30° C.

[0047] [2. Method for manufacturing analytical carriers] Next, a method for manufacturing the analytical support 1 according to this embodiment will be described. The method for manufacturing the analytical support 1 according to this embodiment includes a sintering step and an anodizing step. The method for manufacturing the analytical support 1 may also include a hydration step, if necessary. A sintered material including a sintered body in which a plurality of aluminum metal particles are sintered is obtained by the sintering step. The sintered material may further include a base material. Furthermore, the sintered body is subjected to a hydration step and an anodizing step, if necessary. That is, the sintered material including the sintered body is subjected to a hydration step and an anodizing step, if necessary, to obtain a metal member 10 including a porous body 20. Each step will be described in detail below.

[0048] <Sintering process> In the sintering step, a plurality of aluminum metal particles are sintered to obtain a sintered body, each of which contains at least one of pure aluminum and an aluminum alloy.

[0049] The purity of the pure aluminum may be 99.00% by mass or more, 99.50% by mass or more, 99.80% by mass or more, 99.99% by mass or more, or 99.995% by mass or more. The pure aluminum may contain elements other than aluminum (Al). The elements other than aluminum contained in the pure aluminum may include one or more of silicon (Si), iron (Fe), copper (Cu), manganese (Mn), magnesium (Mg), chromium (Cr), zinc (Zn), titanium (Ti), vanadium (V), gallium (Ga), nickel (Ni), boron (B), zirconium (Zr), and the like. The contents of the elements other than aluminum contained in the pure aluminum may each be less than 1% by mass, or each may be less than 0.01% by mass.

[0050] The aluminum alloy contains aluminum and elements other than aluminum. The elements other than aluminum contained in the aluminum alloy may include one or more of silicon (Si), iron (Fe), copper (Cu), manganese (Mn), magnesium (Mg), chromium (Cr), zinc (Zn), titanium (Ti), vanadium (V), gallium (Ga), nickel (Ni), boron (B), zirconium (Zr), and the like. The total content of the elements other than aluminum contained in the aluminum alloy may be more than 1 mass%. The total content of the elements other than aluminum contained in the aluminum alloy may be 10 mass% or less, or 5 mass% or less. The total content of the elements other than aluminum contained in the aluminum alloy may be 10 mass% or less, or 1 mass% or less. Hereinafter, at least one of pure aluminum and aluminum alloy is also simply referred to as aluminum.

[0051] The aluminum metal particles have an average particle size of 0.1 to 20 μm. The average particle size of the aluminum metal particles before sintering is the D50 value obtained by measuring the particle size distribution on a volume basis by a laser diffraction method. The shape of the particles is not particularly limited, and may be spherical, polygonal, irregular, scaly, fibrous, or the like.

[0052] The aluminum metal particles can be manufactured by a known method. The aluminum metal particles can be manufactured by, for example, an atomizing method, a melt spinning method, a rotating disk method, a rotating electrode method, or other rapid solidification methods. Among these, from the viewpoint of industrial productivity, the aluminum metal particles are preferably manufactured by an atomizing method, and more preferably manufactured by a gas atomizing method. Specifically, the aluminum metal particles are preferably manufactured by atomizing a molten metal.

[0053] The aluminum metal particles may be disposed on at least one surface of the substrate and then sintered. On at least one surface of the substrate, an aluminum powder containing a plurality of aluminum metal particles may be disposed, a green compact obtained by compacting the aluminum powder may be disposed, or a liquid composition such as a slurry containing a plurality of aluminum metal particles may be disposed. The liquid composition may be applied to the surface of the substrate by a known method such as spray coating, brush coating, roller coating, air knife coating, bar coating, spin coating, dipping, or screen printing. The liquid composition may be applied to the desired thickness of the porous body 20, taking into consideration the composition.

[0054] Before disposing the plurality of aluminum metal particles on the surface of the substrate, the surface of the substrate may be pretreated. The pretreatment may include a step of roughening the surface of the substrate. The pretreatment is not particularly limited and may be cleaning, etching, blasting, or the like.

[0055] The substrate may contain a resin or may contain a metal. When the substrate contains a resin, the resin is burned by sintering, so that the substrate can be removed from the analytical carrier 1 after sintering. On the other hand, when the substrate contains a metal, the substrate 50 can be left on the analytical carrier 1. The thickness of the substrate is more than 0 μm. The thickness of the substrate depends on the application, and may be, for example, 1 mm or less, 100 μm or less, 10 μm or less, or 1 μm or less. The metal substrate may be made of the same material as the substrate 50 described above.

[0056] The aluminum powder or composition may contain, in addition to a plurality of aluminum metal particles, a pore former, a binder, a sintering aid, a surfactant, a solvent, etc., as necessary. Any of these may be used that are known in the art.

[0057] The content of aluminum metal particles in the composition is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 31% by mass or more. The content of aluminum metal particles in the composition is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 57% by mass or less.

[0058] The pore-forming material is a material that promotes the formation of voids in the sintered body. The pore-forming material may be, for example, particles containing a polymeric material. The pore-forming material preferably has low solubility in a solvent described below. The polymeric material may contain a polysaccharide or a resin. The polysaccharide may contain, for example, starch. The resin may contain a polyolefin such as polyethylene or polypropylene.

[0059] The average particle diameter of the pore-forming material is preferably 0.1 μm or more and 20 μm or less. By setting the average particle diameter of the pore-forming material to 0.1 μm or more, the average pore diameter can be easily set to 2.5 μm or more. By setting the average particle diameter of the pore-forming material to 20 μm or less, the average pore diameter can be easily set to 20 μm or less. The average particle diameter of the pore-forming material is more preferably 0.5 μm or more, and even more preferably 1 μm or more. In addition, the average particle diameter of the pore-forming material is preferably 10 μm or less, and more preferably 8 μm or less. The average particle diameter of the pore-forming material is the D50 value obtained by measuring the particle size distribution on a volume basis by a laser diffraction method.

[0060] The content of the pore-forming material in the composition is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 12% by mass or more. The content of the pore-forming material in the composition is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 23% by mass or less. When the content of the pore-forming material is equal to or more than the lower limit of the above range, the formation of voids in the sintered body is promoted, and the packing rate of the sintered body is reduced, making it easier to obtain a sintered body having a desired packing rate and a porous body 20 having a desired porosity. In addition, when the content of the pore-forming material is equal to or less than the upper limit of the above range, it is easier to prevent an excessive decrease in the packing rate of the sintered body and to suppress a decrease in the strength of the porous body 20.

[0061] The binder preferably has high solubility in a solvent described later. The binder may contain, for example, synthetic resins such as carboxy-modified polyolefin resin, vinyl acetate resin, vinyl chloride resin, vinyl chloride-vinyl acetate copolymer resin, vinyl alcohol resin, butyral resin, vinyl fluoride resin, acrylic resin, polyester resin, urethane resin, epoxy resin, urea resin, phenol resin, acrylonitrile resin, nitrocellulose resin, paraffin wax, or polyethylene wax, or natural resins such as wax, tar, glue, urushi, rosin, or beeswax. The content of the binder in the composition is preferably 0.5% by mass or more, and more preferably 1% by mass or more. The content of the binder in the composition is preferably 30% by mass or less, and more preferably 20% by mass or less.

[0062] The solvent may contain an organic solvent such as water, ethanol, toluene, ketones, esters, etc. In order to volatilize the solvent, the laminate having the composition applied to the substrate may be dried at a temperature of 20° C. or higher and 300° C. or lower for 1 minute to 30 minutes, if necessary.

[0063] The sintering temperature is not particularly limited, but is preferably 560°C or higher and 660°C or lower. By setting the sintering temperature to 560°C or higher, the strength of the porous body 20 can be improved. By setting the sintering temperature to 660°C or lower, melting of a plurality of aluminum metal particles can be suppressed. The sintering temperature is more preferably 570°C or higher, and even more preferably 580°C or higher. Moreover, the sintering temperature is more preferably 650°C or lower, and even more preferably 620°C or lower.

[0064] The sintering time depends on the sintering temperature, etc., but may be, for example, about 5 hours to 24 hours. The sintering atmosphere is not particularly limited, and may be, for example, any of a vacuum atmosphere, an inert gas atmosphere, an oxidizing gas atmosphere (air), and a reducing gas atmosphere. Among these, the sintering atmosphere is preferably a vacuum atmosphere or a reducing gas atmosphere. The sintering conditions may be any pressure condition of normal pressure, reduced pressure, or increased pressure.

[0065] When the composition contains a pore-forming material, it is preferable to heat the composition at a temperature of 200°C or more and 500°C or less before sintering. By heating the composition at 200°C or more, the pore-forming material can be burned slowly, and more uniformly distributed voids can be formed in the sintered body. By heating the composition at 500°C or less, oxidation of the surface of the aluminum metal particles during heating can be suppressed, and the strength of the porous body 20 can be improved. The heating temperature is preferably 250°C or more, more preferably 280°C or more. The heating temperature is preferably 460°C or less, more preferably 430°C or less.

[0066] The heating time is preferably 5 hours or more and 20 hours or less. By setting the heating time to 5 hours or more, more uniformly distributed voids can be formed in the sintered body. By setting the heating time to 20 hours or less, sintering between the aluminum metal particles is prevented from progressing, and more uniformly distributed voids can be formed in the sintered body. The heating time is more preferably 7 hours or more, and more preferably 15 hours or less. The sintering atmosphere may be any of a vacuum atmosphere, an inert gas atmosphere, and an oxidizing gas atmosphere. In addition, the sintering conditions may be any of pressure conditions of normal pressure, reduced pressure, and increased pressure.

[0067] The sintering step may include a first sintered layer forming step for obtaining a first sintered layer and a second sintered layer forming step for obtaining a second sintered layer. In the first sintered layer forming step, a plurality of aluminum metal particles may be sintered to obtain a first sintered layer. As described above, the plurality of aluminum metal particles may be arranged on at least one surface of the base material and then sintered. In the second sintered layer forming step, a laminate in which a plurality of aluminum metal particles are arranged on the surface of the first sintered layer may be sintered. In the first sintered layer forming step and the second sintered layer forming step, at least one of the average particle size, aspect ratio, or constituent material of the plurality of aluminum metal particles used, the composition of the composition, or the type or average particle size of the pore-forming material may be different.

[0068] The filling rate of the sintered body is 20% by volume to 70% by volume. By setting the filling rate of the sintered body to 20% by volume or more, it is easy to obtain a porous body 20 having a porosity of the desired range or less after the anodizing process. This makes it possible to suppress peeling of aluminum metal particles from the porous body 20, and improve the strength of the porous body 20. Furthermore, by setting the filling rate of the sintered body to 70% by volume or less, it is easy to obtain a porous body 20 having a porosity of the desired range or more after the anodizing process. This makes it possible to improve the suction performance of the porous body 20. The filling rate may be 30% by volume or more, 40% by volume or more, or 50% by volume or more. Furthermore, the filling rate may be 65% by volume or less, 60% by volume or less, or 55% by volume or less. The filling rate can be obtained by dividing the mass of the sintered body portion, which is obtained by subtracting the mass of the base material portion from the mass of the entire sintered material, by the mass of the sintered body portion when the filling rate is assumed to be 100%, as described in the Examples section below.

[0069] <Hydration process> The manufacturing method of the analytical carrier 1 according to the present embodiment may include a hydration step before the anodization step. The hydration step is a step for efficiently forming an anodized film by forming a hydration film on the surface of aluminum metal particles, and converting the hydration film into an oxide film during the subsequent anodization step. At the same time, there is an effect of lifting and cleaning dirt present on the aluminum surface before anodization from the aluminum surface, and when an anodized film is subsequently applied, the occurrence of unevenness in the appearance can be suppressed. In addition, the occurrence of fluorescence derived from organic matter attached to the aluminum surface can be suppressed. The hydration step is a step for heat-treating the sintered body with warm water such as boiling water. The warm water may be pure water, or may be an aqueous phosphoric acid solution in which phosphoric acid is dissolved. The concentration of the aqueous phosphoric acid solution may be, for example, 0.001 mL / L to 5 mL / L. The aqueous phosphoric acid solution of this concentration can be obtained, for example, by adjusting an 85 mass % aqueous phosphoric acid solution with pure water to a desired concentration. The addition of phosphoric acid enhances the cleaning effect of the surface. When the sintered body is subjected to a hydration treatment, a hydration film of aluminum hydroxide is formed on the surface of the aluminum, and as described above, the hydration film may be included in the outer shell 24, but the outer shell 24 may also include a hydration film.

[0070] <Anodizing process> In the anodization process, the sintered body is anodized to form an outer shell 24 including an anodized film on the surface of the aluminum metal particle. In the anodization process, for example, an anode on which the sintered body is placed and a cathode on which stainless steel (SUS) is placed are immersed in an electrolyte to perform electrolysis.

[0071] In the anodization step, the sintered body may be anodized using an electrolytic solution containing an organic acid. By anodizing the sintered body using an electrolytic solution containing an organic acid, the above-mentioned organic acid anodized film can be formed. In the anodization step, the sintered body may be anodized using an electrolytic solution containing at least one selected from the group consisting of citric acid, adipic acid, oxalic acid, and salts thereof. Examples of these salts include ammonium salts, sodium salts, potassium salts, and silicates. By anodizing the sintered body using an electrolytic solution containing at least one of citric acid and a citrate, the above-mentioned citric acid anodized film can be formed. By anodizing the sintered body using an electrolytic solution containing at least one of adipic acid and an adipic acid salt, the above-mentioned adipic acid anodized film can be formed. By anodizing the sintered body using an electrolytic solution containing at least one of oxalic acid and an oxalate, the above-mentioned oxalic acid anodized film can be formed.

[0072] In the anodization step, the sintered body may be anodized using an electrolytic solution containing an inorganic acid. By anodizing the sintered body using an electrolytic solution containing an inorganic acid, the above-mentioned inorganic acid anodized film can be formed. In the anodization step, the sintered body may be anodized using an electrolytic solution containing at least one selected from the group consisting of sulfuric acid, phosphoric acid, and boric acid, and salts thereof. Examples of these salts include ammonium salts, sodium salts, potassium salts, and silicates. By anodizing the sintered body using an electrolytic solution containing at least one of sulfuric acid and a sulfate, the above-mentioned sulfuric acid anodized film can be formed. By anodizing the sintered body using an electrolytic solution containing at least one of phosphoric acid and a phosphate, the above-mentioned phosphoric acid anodized film can be formed. By anodizing the sintered body using an electrolytic solution containing at least one of boric acid and a borate, the above-mentioned boric acid anodized film can be formed.

[0073] In the anodization step, an electrolyte solution containing a weak acid may be used for anodization. When a strong acid such as sulfuric acid is used, if the strong acid remains in the porous body 20, the strong acid may cause the protein to denature due to the loss of binding bonds (functional groups) of the protein adsorbed to the porous body 20 or the change in three-dimensional structure. In such a case, the signal intensity from the label such as a fluorescent substance may decrease, and the SN ratio may decrease. Therefore, the SN ratio can be improved by using an electrolyte solution containing a weak acid. In this specification, a weak acid has an acid dissociation constant pKa of more than 1.2, preferably more than 1.8, and more preferably more than 3.0, measured at 25°C.

[0074] In the anodization step, an electrolyte solution containing at least one acid selected from the group consisting of citric acid, adipic acid, oxalic acid, phosphoric acid, and boric acid may be used for the anodization. An electrolyte solution containing such a weak acid is unlikely to denature proteins, and therefore can suppress a decrease in the signal intensity from a label such as a fluorescent substance. As a result, the signal-to-noise ratio can be improved.

[0075] The conditions of the anodization are not particularly limited. For example, the electrolysis temperature may be 0°C or higher, 10°C or higher, 20°C or higher, 30°C or higher, 40°C or higher, or 50°C or higher. The electrolysis temperature may be 70°C or lower, 60°C or lower, or 50°C or lower. The electrolysis voltage may be 0.1V or higher, or 1V or higher, depending on the type of electrolytic solution. The electrolysis voltage may be 500V or lower, or 400V or lower, depending on the type of electrolytic solution. The electrolysis time may be 0.1 minutes or more, or 1 minute or more. The electrolysis time may be 60 minutes or less, or 20 minutes or less. The anodization may be performed in a single step, or may be performed in a plurality of different steps.

[0076] As described above, the method for producing an analytical support 1 according to this embodiment is a method for producing an analytical support 1 provided with a metal member 10 including a porous body 20. The porous body 20 includes a skeleton 22 formed by an assembly of a plurality of aluminum particles 21, and a plurality of voids 23 surrounded by the skeleton 22. The skeleton 22 has an outer shell 24 including an anodized film containing aluminum oxide on the surface of the aluminum particle 21. The production method includes a sintering step of sintering a plurality of aluminum metal particles to obtain a sintered body, and an anodizing step of anodizing the sintered body to form an outer shell 24 including an anodized film on the surface of the aluminum metal particle. The average particle diameter of the plurality of aluminum metal particles is 0.1 μm to 20 μm. The packing rate of the sintered body is 20 vol % to 70 vol %. The organic acid concentration of the metal member 10 is 150 mg / m 2 / 100μm or less.

[0077] [3. Analysis method] The analytical method according to this embodiment is an analytical method for analyzing an analyte supported on an analytical carrier 1. Examples of the analyte include amino acids, peptides, proteins, genes, sugars, lipids, cells, and complexes thereof. More specifically, examples of the analyte include peptides such as PCT (procalcitonin); proteins such as urinary albumin; hormones such as HCG (human chorionic gonadotropin) and LH (luteinizing hormone); HBs antigen, rotavirus antigen, adenovirus antigen, RSV (Respiratory Syndrome), and the like. Antigens or antibodies of viral infections such as HBs antibody, HCV (Hepatitis C virus) antibody, HIV antibody, EBV antibody, RSV antibody, rubella virus antibody, measles virus antibody, enterovirus antibody, dengue virus antibody, and SARS antibody; antigens or antibodies of bacterial infections such as pneumococcus antigen, mycoplasma antigen, group A hemolytic streptococcus antigen, legionella antigen, tuberculosis antigen, gonococcus antigen, tetanus antigen, mycoplasma antibody, Helicobacter pylori antibody, and tuberculosis antibody; antigens or antibodies of chlamydia infections such as chlamydia antigen; antigens or antibodies of spirochete infections such as Treponema pallidum antibody; antigens or antibodies of protozoal diseases such as malaria antibody and toxoplasma antibody.

[0078] The analysis method includes an irradiation step of irradiating light and a detection step of detecting the light.

[0079] <Irradiation process> In the irradiation step of irradiating light, the analytical carrier 1 carrying the analyte is irradiated with light having at least one wavelength included in the ultraviolet to infrared regions. The irradiated light is also called incident light incident on the analytical carrier 1. The irradiated light may include a light beam or may be a light beam. The irradiated light may have a continuous wavelength, a discontinuous wavelength, or a single wavelength.

[0080] The irradiated light may have a wavelength included in at least one region selected from the group consisting of the ultraviolet region, the visible region, and the infrared region. The wavelength of the ultraviolet region may be 10 nm or more and less than 380 nm, the wavelength of the visible region may be 380 nm or more and less than 780 nm, and the wavelength of the infrared region may be 780 nm or more and less than 1 mm. That is, the irradiated light may have any wavelength within the range of 10 nm or more and less than 1 mm. The excitation light may have a continuous wavelength, a discontinuous wavelength, or a single wavelength.

[0081] The light in the ultraviolet region may include at least one of near ultraviolet light and vacuum ultraviolet light. The near ultraviolet light may include light having a wavelength of 200 nm or more and less than 380 nm. The vacuum ultraviolet light may include light having a wavelength of 10 nm or more and less than 200 nm. The near ultraviolet light may include at least one selected from the group consisting of UVA, UVB, and UVC. The UVA may include light having a wavelength of 315 nm or more and less than 380 nm. The UVB may include light having a wavelength of 280 nm or more and less than 315 nm. The UVC may include light having a wavelength of 200 nm or more and less than 280 nm.

[0082] The light in the infrared region may include at least one selected from the group consisting of near infrared, mid infrared, and far infrared. The near infrared may include light having a wavelength of 780 nm or more and less than 2.5 μm. The mid infrared may include light having a wavelength of 2.5 μm or more and less than 4 μm. The far infrared may include light having a wavelength of 4 μm or more and less than 1 mm.

[0083] The light can be provided by a light source, which may include, for example, an LED, a laser diode, an incandescent lamp, a halogen lamp, a tungsten lamp, a xenon lamp, a halogen lamp, a metal halide lamp, or a high pressure mercury lamp.

[0084] <Detection process> The detection step of detecting light is a step of detecting at least one type of outgoing light selected from the group consisting of reflected light, scattered light, transmitted light, fluorescence, and phosphorescence of irradiated light. By detecting the intensity of such light with a detector, information on the analytical carrier 1 in a state in which the analyte is supported can be obtained. The detector may obtain one-dimensional information (point information), two-dimensional information (line information), or three-dimensional information (stereoscopic space information) on the analytical carrier 1 in a state in which the analyte is supported. The detector may detect the wavelength to be detected, and may detect light by cutting unnecessary light through a filter or the like. The detection of the outgoing light may be performed visually by observing the outgoing light emitted from the analytical carrier 1 with the naked eye.

[0085] The detector may be one having a light receiving element such as a photomultiplier tube (PMT), a photodiode (PD), a complementary metal oxide semiconductor (CMOS) sensor, or a charge coupled device (CCD) sensor. The detector may output the detection result of the detected light to an output unit. The output unit may be, for example, a liquid crystal display, a CRT, or a printer.

[0086] [4. Test kits] Next, an example of a test kit using the analytical carrier 1 will be described. The test kit may also be called a diagnostic kit. As shown in FIG. 3, the test kit includes a test strip 100 having the analytical carrier 1. Specifically, the test strip 100 includes the analytical carrier 1, a specimen supplying section 110, and an absorbing section 130. The analytical carrier 1 is provided with a determination section 120. The test kit further includes a case (not shown in the drawings) for storing the test strip 100.

[0087] The specimen supplying section 110 may contain, for example, a labeled antibody that specifically binds to an antigen that is the subject of analysis. Examples of subjects of analysis by the test kit include the same as the subjects of analysis described above. A specimen collected from a living body or the like is supplied to the specimen supplying section 110 and mixed with the labeled antibody to form a mixed liquid. The mixed liquid is developed to the determination section 120 by capillary action of the analytical carrier 1, and excess specimen is absorbed by the absorption section 130.

[0088] The determination unit 120 has, for example, a test line and a control line. For example, a capture antibody that specifically binds to the analyte is fixed to the test line. When the analyte is contained in the sample, a labeled antibody is fixed to the capture antibody on the test line via the analyte. For example, an antibody that specifically binds to the labeled antibody is fixed to the control line. When the mixture containing the sample and the labeled antibody is developed to the control line, the labeled antibody binds to the antibody fixed to the control line.

[0089] The labeled antibody contains a label including particles such as fluorescent beads, and an antibody that binds to the label to form a complex and specifically binds to the analyte. Therefore, if there is a location where the concentration or density of the labeled antibody is high, the label will be concentrated and the fluorescence of this location can be confirmed. Therefore, the test kit can be used to test for a positive result when fluorescence is confirmed in both the test line and the control line, and for a negative result when fluorescence is confirmed only in the control line.

[0090] The fluorescent beads can emit fluorescence in response to excitation light. As described above, the excitation light may be light having at least one wavelength included in the ultraviolet region to the infrared region. The average particle size of the particles may be 10 nm or more and 100 nm or less. When the average particle size is within the above range, the particles can flow smoothly through the porous body 20. The average particle size may be 70 nm or less, or 50 nm or less. The average particle size of the particles is the D50 value obtained by measuring the particle size distribution on a volume basis by a laser diffraction method.

[0091] The fluorescence can be detected by, for example, a fluorescence detector such as a fluorescence scanner. With the fluorescence scanner, the analytical support 1 carrying the analyte is irradiated with excitation light, and the fluorescence of the fluorescent beads excited by the excitation light can be detected.

[0092] The test kit can be used, for example, for infectious disease testing; genetic analysis; pregnancy testing; livestock testing; and allergen testing for foods, animals, plants, metals, house dust, etc.

[0093] [5.Other] In the above-mentioned embodiment, the analytical carrier 1 is used in a test strip 100 and a test kit that utilize immunochromatography. The analytical carrier 1 can be used appropriately as long as it is used in an analytical method for analyzing an analyte supported on the analytical carrier 1, in which incident light is irradiated onto the analytical carrier 1 and light emitted from the analytical carrier 1 is detected. In this case, lateral flow on the analytical carrier 1 is not essential.

[0094] In the above-mentioned embodiment, an example in which the analyte contains an antigen and the label is bound to the antibody has been described, but the present invention is not limited to such an example. For example, the analyte may contain an antibody and the label may be bound to the antigen. In addition, an example in which a complex is formed by utilizing an antigen-antibody reaction between an antigen and an antibody has been described, but the present invention is not limited to such an example. For example, a complex formed by the interaction of biological materials, such as the bond between biotin and avidin, may be used.

[0095] The analytical carrier 1 can also be used as, for example, a gas or liquid separation membrane; a moisture absorbing material; a water absorbing material; an adsorption material for adsorbing foreign matter such as pollen, particulate matter, bacteria, odor components, and heavy metals; a wiping sheet; a test sheet for drugs such as concentrated sulfuric acid, for urine testing, and for pH testing; a material for disinfection and sterilization; a reflecting material (standard white plate); a separator for batteries and electric double layer capacitors; a catalyst carrier; a reaction field for synthesis reactions; and a heat insulating material. Examples of the separation membrane include a reverse osmosis membrane, an ion exchange membrane, and a gas separation membrane. Examples of the adsorption material include a mask, a filtration membrane, and a filter. EXAMPLES

[0096] The present embodiment will be described in more detail below with reference to examples, comparative examples and reference examples, but the present embodiment is not limited to these.

[0097] [Example 1] (Slurry preparation) First, 34 parts by mass of aluminum metal particles, 19 parts by mass of a pore former, and 1 part by mass of a binder were uniformly dispersed in 46 parts by mass of a solvent to prepare a slurry. The aluminum metal particles (AHZL58FN manufactured by Toyo Aluminum Co., Ltd.) were pure aluminum (JIS A1080) with a purity of 99.80% by mass or more. The aluminum metal particles were approximately spherical and had an average particle diameter of 3 μm. As the pore former, starch (Nikka Co., Ltd., Nikka Co., Ltd., Nikka Co., Ltd., Nikka Co., Ltd., Nikka Co., Ltd., Nikka Co., Ltd., Nikka Co., Ltd.) with an average particle diameter of 7 μm was used. As the binder, an ethyl cellulose-based resin was used. As the solvent, butyl acetate was used.

[0098] (Sintering) The slurry was applied to one surface of an aluminum substrate having a thickness of 30 μm using a Comma Coater (registered trademark) manufactured by Hirano Tecseed Co., Ltd., so that the thickness of the porous body was 50 μm. The slurry was dried at 100°C for 1.5 minutes, heated at 350°C for 5 hours in an air atmosphere, and then sintered at 620°C to 640°C for 10 hours in an argon gas atmosphere. In this way, a sintered material in which a sintered body was provided on an aluminum substrate was produced.

[0099] (Hydration treatment) Next, the sintered material was washed with pure water at room temperature for 10 seconds. After that, the sintered material was immersed in an aqueous solution of 85% phosphoric acid adjusted to 0.5 mL / L with pure water at 85°C for 3 minutes to perform hydration treatment. Next, the hydrated sintered material was washed with pure water at room temperature for 30 seconds.

[0100] (Anodizing) Next, the hydrated sintered material was anodized to form an outer shell containing aluminum oxide on the surface of the aluminum metal particles. Specifically, the sintered material placed on the anode and stainless steel (SUS) placed on the cathode were immersed in an electrolyte at 50°C prepared with pure water to have 4g / L of citric acid and 0.2g / L of triammonium citrate. Then, anodization was performed at a voltage of 1V for 5 minutes.

[0101] After the anodization treatment, the obtained metal member was washed with pure water at room temperature for 30 seconds and dried for 15 minutes at 50° C. In this manner, an analytical support according to this example was obtained.

[0102] [Example 2] An analytical support was prepared in the same manner as in Example 1, except that the electrolysis voltage for anodization was changed to 5V.

[0103] [Example 3] An analytical support was prepared in the same manner as in Example 1, except that the electrolysis voltage for anodization was changed to 60V.

[0104] [Example 4] An analytical carrier was prepared in the same manner as in Example 3, except that a slurry was prepared by uniformly dispersing 34 parts by mass of aluminum metal particles, 17 parts by mass of a pore-forming material, and 1 part by mass of a binder in 48 parts by mass of a solvent.

[0105] [Example 5] An analytical support was produced in the same manner as in Example 3, except that 54 parts by mass of aluminum metal particles and 19 parts by mass of binder were uniformly dispersed in 27 parts by mass of solvent to prepare a slurry.

[0106] [Example 6] An analytical support was produced in the same manner as in Example 3, except that 64 parts by mass of aluminum metal particles and 1 part by mass of binder were uniformly dispersed in 35 parts by mass of solvent to prepare a slurry.

[0107] [Example 7] An analytical carrier was prepared in the same manner as in Example 3, except that AHU091 (trade name, manufactured by Toyo Aluminum Co., Ltd.) having an average particle size of 1.8 μm was used as the aluminum metal particles.

[0108] [Example 8] An analytical carrier was prepared in the same manner as in Example 3, except that aluminum metal particles having an average particle size of 5 μm and sold under the trade name AHZ58CN by Toyo Aluminum KK were used.

[0109] [Example 9] An analytical support was prepared in the same manner as in Example 3, except that aluminum metal particles having an average particle size of 15 μm (trade name: AHZ530C, manufactured by Toyo Aluminum Co., Ltd.) were used and the electrolysis voltage for anodization was set to 15 V.

[0110] [Example 10] An analytical support was prepared in the same manner as in Example 8, except that the slurry was applied to one surface of the aluminum substrate so that the porous body had a thickness of 100 μm.

[0111] [Example 11] An analytical support was prepared in the same manner as in Example 1, except that the electrolyte for anodization was prepared with pure water so that the concentration of ammonium dihydrogen phosphate was 1 g / L.

[0112] [Example 12] An analytical support was prepared in the same manner as in Example 11, except that the electrolysis voltage for anodization was changed to 5V.

[0113] [Example 13] An analytical support was prepared in the same manner as in Example 11, except that the electrolysis voltage for anodization was changed to 60V.

[0114] [Example 14] An analytical support was prepared in the same manner as in Example 11, except that the electrolysis voltage for anodization was changed to 150V.

[0115] [Example 15] An analytical support was prepared in the same manner as in Example 11, except that the electrolysis voltage for anodization was changed to 400V.

[0116] [Example 16] An analytical support was prepared in the same manner as in Example 14, except that the electrolyte for anodization was prepared with pure water so as to have adipic acid of 5 g / L and ammonium adipate of 100 g / L.

[0117] [Example 17] An analytical support was prepared in the same manner as in Example 14, except that the electrolyte for anodization was prepared with pure water so as to have a boric acid concentration of 80 g / L and an ammonium pentaborate octahydrate concentration of 0.7 g / L.

[0118] [Example 18] An analytical support was prepared in the same manner as in Example 1, except that the electrolyte for anodization was prepared with pure water to have a sulfuric acid concentration of 150 g / L, the electrolysis temperature was 10° C., the electrolysis voltage was 10 V, and the electrolysis time was 6 minutes.

[0119] [Example 19] An analytical support was prepared in the same manner as in Example 18, except that the electrolysis time for anodization was set to 1 minute.

[0120] [Example 20] An analytical support was prepared in the same manner as in Example 18, except that the electrolysis time for anodization was set to 20 minutes.

[0121] [Example 21] The electrolyte for anodization was prepared by mixing 85% by mass phosphoric acid aqueous solution with pure water to give a concentration of 40 mL / L. An analytical support was prepared in the same manner as in Example 1, except that the electrolysis temperature was 25°C, the electrolysis voltage was 10 V, and the electrolysis time was 6 minutes.

[0122] [Example 22] An analytical support was prepared in the same manner as in Example 1, except that the electrolyte for anodization was prepared with pure water to have an oxalic acid concentration of 50 g / L, the electrolysis temperature was 25°C, the electrolysis voltage was 10 V, and the electrolysis time was 8 minutes.

[0123] [Comparative Example 1] An analytical support was prepared in the same manner as in Example 1, except that the electrolysis voltage for anodization was changed to 150V.

[0124] [Comparative Example 2] An analytical support was prepared in the same manner as in Example 1, except that the electrolysis voltage for anodization was changed to 400V.

[0125] [Comparative Example 3] An analytical support was prepared in the same manner as in Example 22, except that the electrolysis time for anodization was changed to 23 minutes.

[0126] [Comparative Example 4] An analytical support was prepared in the same manner as in Example 22, except that the electrolysis voltage for anodization was changed to 30 V and the electrolysis time to 1 minute.

[0127] [Reference example 1] A nitrocellulose membrane filter FF80HP manufactured by Cytiva was used as the analytical carrier in this example.

[0128] [evaluation] The analytical carriers of the respective examples were subjected to the following evaluations.

[0129] (Filling rate) The packing ratio of the sintered body was obtained by measuring the sintered material before hydration treatment according to the following procedure. - 100cm projected area from sintered material 2The measurement sample was then cut out. After that, measurements and calculations were performed on the measurement sample. (Note that in this specification, the projected area refers to the horizontal projected area of ​​a sintered material, a sintered body, a porous body, a metal member, an analytical carrier, a measurement sample, etc., when viewed in a planar view in the same direction as the thickness direction.) The mass Ma (g) of the entire sintered material, including the sintered body and the base material, was measured. The overall thickness Wa (cm) of the sintered body was measured with a micrometer. The thickness Wb (cm) of the substrate was measured with a micrometer. The mass of the substrate part, Mb (g), was calculated as Mb = substrate density × Wb × 100. In this embodiment, the density of the base material and the sintered body portion made of aluminum material is set to 2.7 g / cm 3 The calculation was done as follows. The mass of the sintered body, Mc (g), was calculated as Mc = Ma - Mb. The mass Md (g) of the sintered part when the filling rate is assumed to be 100% was calculated as follows: Md = density of material of sintered part × (Wa-Wb) × projected area of ​​sintered part = 2.7 × (Wa-Wb) × 100. The packing ratio of the sintered body contained in the measurement sample was calculated as packing ratio (%) = (Mc / Md) x 100.

[0130] (Structure of anodized film) After cutting the analytical support, the cut surface was mirror-finished using a Cross Section Polisher (registered trademark) manufactured by JEOL Ltd., and the cross section was observed using a ULTRA plus scanning electron microscope manufactured by Carl Zeiss K.K. to confirm the structure of the anodized film.

[0131] (Porosity) The porosity of the porous body was obtained by carrying out measurements on the analytical carrier according to the following procedure. All work was carried out at room temperature. The cock of the burette to be used was previously coated with vacuum grease. 5 mL of pure water (room temperature) was placed in a 10 mL burette (±0.02 mL) with a minimum graduation interval of 0.05 mL. The total thickness W1 (cm) of the analytical support, including the porous body and the base material, was measured with a micrometer. The thickness W2 (cm) of the non-porous portion of the analytical carrier (base material) was measured with a micrometer. The thickness of the porous part W3 = W1 - W2 (cm) was calculated. The apparent volume of the porous body is W3 (cm) × projected area A (cm 2 )=1.00cm 3 A measurement sample with a projected area A was cut out so that: The measurement sample for projected area A was cut into approximately 5 mm squares. All of the cut measurement samples were gently placed in a burette containing water and completely submerged. A rubber hose was connected to the nozzle of the burette and a vacuum was applied for 1 minute using a vacuum pump to expel the air from the voids in the porous sample. Remove the rubber hose and read the liquid level after vacuuming (to 1 / 10 of the minimum scale). The difference between the height of the liquid after evacuation and the liquid level before the sample was submerged is used to calculate the volume of water V1 (cm3), which corresponds to the volume of the solid part contained in the entire measurement sample. 3 ) was sought. The volume of the substrate other than the porous body is V2 = A × W2 (cm 3 ) was calculated. - Volume of the solid part of the porous body, excluding voids, V3 (cm 3 ) was calculated as V3 = V1 - V2. The pore volume V4 occupied by the voids in the porous body is V4 = 1.00 cm 3 -V3(cm 3 ) was calculated. The porosity of the porous body contained in the measurement sample was calculated as porosity (%) = (V4 / 1.00) x 100.

[0132] (Thickness of anodized film) After cutting the analytical support, the cut surface was mirror-finished with a Cross Section Polisher (registered trademark) manufactured by JEOL Ltd. to obtain a sample for film thickness measurement. The cross section of the sample for film thickness measurement was observed with a scanning electron microscope ULTRA plus manufactured by Carl Zeiss Co., Ltd. to measure the film thickness of the anodized film.

[0133] (Flow Rate) The flow rate was measured as follows. First, the analytical carrier was immersed in pure water so that the plane direction of the analytical carrier was perpendicular to the liquid surface. Then, the time it took for the water to be sucked up to a height of 4 cm from the liquid surface by capillary action after immersion of the analytical carrier in pure water was measured and evaluated as the flow rate.

[0134] (Ion analysis) The anions and cations extracted from the analytical carrier were quantified by ion analysis using a calibration curve prepared in advance as follows. Specifically, acetate ions, formate ions, citrate ions, adipate ions, oxalate ions, phosphate ions, and sulfate ions were quantified as anions by ion chromatography. Also, boron ions were quantified as cations by ICP emission spectrometry.

[0135] Calibration curve used in ion chromatography When measuring the anions listed in Table 1 by ion chromatography, each reagent (standard solution) was diluted to prepare solutions of multiple concentrations, and a calibration curve for each anion was prepared.

[0136] [Table 1]

[0137] ·extraction First, 40 analytical carriers cut into approximately 10 mm squares were prepared. 2 (0.0040m 2) was cut into approximately 10 mm squares to prepare samples for measurement. These analytical supports were placed in a 100 mL screw-cock bottle, and then approximately 50 mL of 10 mM KOH aqueous solution was added. The bottle was placed in an ultrasonic cleaner (US CLEANER (US-2R) manufactured by AS ONE Corporation) and the ultrasonic cleaner was operated at high output for 20 minutes. The extract thus obtained was transferred to a measuring flask and made up to 100 mL with 10 mM KOH aqueous solution, which was used as the analytical sample.

[0138] Anion measurement The anions in the analytical sample were quantified by ion chromatography using the following apparatus and conditions: Measurement sample: the analytical sample obtained as described above Apparatus: Dionex® Integrion® (Thermo Fisher Scientific Inc.) Column: IonPac (registered trademark) AG-11 (Thermo Fisher Scientific Co., Ltd.) Suppressor: Thermo Scientific Dionex AERS500e (Thermo Fisher Scientific, Inc.) Eluent: KOH Separation condition: Gradient Column temperature: 40℃ Suppressor temperature: 20℃

[0139] - Calculation of anion concentration The measured values ​​(mg / L) of anions obtained by ion chromatography were 2 The anion concentration was calculated by the following formula (1): When the measured value was below the lower limit of quantification, the measured value of the anion was calculated as 0 mg / L.

[0140] Concentration of anion (mg / m 2 / 100 μm) = measured value (mg / L) × amount of sample for analysis (0.100 L) / {projected area of ​​the porous body of the analytical support (0.0040 m 2 ) × (thickness of porous body (μm) / 100)} (1)

[0141] Measurement of cations The cations in the analytical sample were quantified by ICP emission spectrometry. The equipment and conditions used for ICP emission spectrometry are as follows: Measurement sample: The anion analysis sample diluted 2-fold with pure water Equipment: High-resolution ICP analyzer SPS3100 (SII Nano Technology Co., Ltd.) High frequency output: 1.2kw PMT voltage: High Wavelength: 249.774nm BG position: 249.787nm Integration times: 3 Accumulation time: 1 second

[0142] Calculation of cation concentration The measured values ​​(mg / L) of cations obtained by ICP emission spectrometry were 2 The concentration of cations was calculated using the following formula (2). The molar mass of boric acid was 61.83 g / mol, and the molar mass of boron was 10.811 g / mol. When the measured value was below the lower limit of quantification, the measured value of the cation was calculated as 0 mg / L.

[0143] Boric acid equivalent concentration (mg / m 2 / 100 μm) = (measured boron concentration (mg / L) × 61.83 / 10.811) × amount of sample for analysis (0.100 L) × 2 / {projected area of ​​porous body of analytical support (0.0040 m 2 ) × (thickness of porous body (μm) / 100)} (2)

[0144] Calibration curve used in ICP atomic emission spectrometry When measuring the cations listed in Table 2 by ICP atomic emission spectrometry, the reagents (standard solutions) were diluted to prepare solutions of a number of concentrations, and calibration curves for the cations were prepared.

[0145] [Table 2]

[0146] (autofluorescence and S / N ratio) (1) Preparation of reagents and materials First, the following reagents and materials were prepared. 1×PB (1×Phosphate Buffer) Na2HPO4·12H2O (Wako Pure Chemical Industries, #197-02865) 2.9g KH2PO4 (Wako Pure Chemical Industries, #169-04245) 0.2g Mix Na2HPO4·12H2O and KH2PO4 and dilute to 1L with pure water. 1 x PBS (1 x Phosphate Buffered Saline) NaCl (Wako Pure Chemical Industries, #191-01665) 8.0g Na2HPO4·12H2O (Wako Pure Chemical Industries, #197-02865) 2.9g KCl (Wako Pure Chemical Industries, #163-03545) 0.2g KH2PO4 (Wako Pure Chemical Industries, #169-04245) 0.2g Mix NaCl, Na2HPO4·12H2O, KCl and KH2PO4 and dilute to 1L with pure water. 1 x TBS-T (1 x Tris-Buffered Saline with Tween20) Tris(hydroxymethyl)aminomethane (Dojindo Laboratories, #35401-25) 6.1g NaCl (Wako Pure Chemical Industries, #191-01665) 8.1g KCl (Wako Pure Chemical Industries, #163-03545) 0.2g Tris(hydroxymethyl)aminomethane, NaCl, and KCl are mixed and dissolved in 900 mL of pure water, and then HCl is added to prepare a first preparation solution adjusted to pH 8.0. Add 0.5 mL of Tween 20 to the first preparation to prepare the second preparation. Dilute the second solution to 1L with pure water. Simulated serum (2% BSA, 0.05% Tween 20 in 1x PBS) Antibody for membrane fixation: Human IgG derived from human serum (Sigma-Aldrich, I4506) Fluorescent labeled antibody for 488nm: Goat Anti-Human IgG(H+L)Alexa Fluor488(Thermo Scientific,A11013) Fluorescent labeled antibody for 532nm: Goat Anti-Human IgG(H+L)Alexa Fluor555(Thermo Scientific,A21433) Absorbent pad: Cellulose Fiber Sample Pads 20×300mm 100PK (Merck Millipore, CFSP203000) Backing sheet: Pre-cut backing sheet (Nippon Engineering, 34042 / 11GL-56338)

[0147] (2) Preparation of antibody-immobilized test strips Next, a test strip with an antibody immobilized thereon was prepared as follows. This test strip is a test piece for measuring the S / N ratio described later. The analytical carrier was cut with scissors to a size of 25 mm in length and 5 mm in width, and used as a membrane for evaluation. The antibody for membrane immobilization was diluted with 1×PBS to a concentration of 1 mg / mL to prepare an antibody solution for immobilization. 0.5 μL of the antibody solution for immobilization was dropped at positions 12 mm (first spot) and 20 mm (second spot) from the bottom end of the membrane using a microsyringe with a capacity of 2 μL at a constant discharge speed of 0.2 μL / min using a syringe pump. The dropped antibody solution for immobilization was naturally dried. The membrane was placed in a glass petri dish and placed in a thermostatic bath set at 50° C. for 30 minutes to immobilize the antibody to the membrane. The membrane was attached to a backing sheet cut to a size of 60 mm in length and 5 mm in width. The absorbent pad was attached to the backing sheet so that the upper end of the membrane and the lower end of the absorbent pad, cut to a size of 20 mm in length and 5 mm in width, overlapped by about 2 mm. The remaining part of the backing sheet was cut off, and the test strip was made to a length of about 43 mm.

[0148] (3) Flow test Next, a flow test was performed according to the following procedure. A fluorescently labeled antibody corresponding to the wavelength to be measured was diluted with a predetermined amount of pseudo serum to a concentration of 1 μg / mL to prepare a fluorescently labeled antibody solution. 100 μL of the fluorescently labeled antibody solution was placed in each well of the module plate. The test strip was held upright for 15 minutes so that the lower end of the membrane of the test strip was immersed in the fluorescently labeled antibody solution in the well by about 2 mm and the absorbent pad was on the upper side. The test strip was removed from the well, and a 4-well plate containing 5 mL each of 1×TBS-T, 1×TBS-T, 1×PB, and pure water was placed on a shaker, and the test strip was washed by shaking each of the liquids in the order of the above for 5 minutes each. After washing the test strip, the test strip was naturally dried while being shielded from light on a JK Wiper 150-S (Nippon Paper Crecia Co., Ltd.).

[0149] (4) Preparation of test strips for measuring autofluorescence Next, a test strip for measuring autofluorescence was prepared. The test strip for measuring autofluorescence was prepared in the same manner as the test strip for measuring S / N ratio, except that the antibody fixation and the flow test were not performed. That is, the test strip for measuring autofluorescence was prepared using an evaluation membrane cut into a predetermined size from the analytical carrier, and was directly used for measuring autofluorescence.

[0150] (5) Autofluorescence Measurement Using a fluorescence scanner (Cytiva, Amersham Typhoon scanner RGB system), the test strip for measuring autofluorescence was irradiated with excitation light, and the fluorescence intensity (count number) of the test strip was measured. The voltage applied to the photomultiplier tube (PMT) was set to 400V, and scanning was performed under the condition of a pixel size of 100 μm. In addition, the fluorescence intensity was measured when two patterns of excitation wavelengths, 488 nm and 532 nm, were used. When the wavelength of the excitation light was 488 nm, the wavelength of the fluorescence to be measured was 525 nm. When the wavelength of the excitation light was 532 nm, the wavelength of the fluorescence to be measured was 570 nm. The measurement area of ​​the autofluorescence was a central 3 mm square area set at a position between the first spot part and the second spot part in the length direction of the membrane and 1 mm apart from both ends of the membrane in the width direction. The intensity of the autofluorescence was obtained by calculating the average value of the intensity of all pixels in this measurement area. As an example, scanning images of the test strips for measuring autofluorescence according to Example 3 and Reference Example 1 at an excitation wavelength of 488 nm are shown in Fig. 4. Scanning images of the test strips for measuring autofluorescence according to Example 3 and Reference Example 1 at an excitation wavelength of 532 nm are shown in Fig. 5.

[0151] (6) Measurement of autofluorescence of a standard reflector The autofluorescence of the standard reflector was measured under the same conditions as those for the test strip for measuring the autofluorescence (Reference Example 2). The standard reflector used was an Al standard reflector (product name: Φ20 reference plate (2 pieces), model: FAV02) (Lot No. Al-S-29) manufactured by Otsuka Electronics Co., Ltd. The autofluorescence of each analytical carrier was calculated as a relative value based on the measured value of the autofluorescence of the standard reflector. The pass standard was a relative value of 2.0 or less.

[0152] (7) S / N ratio measurement Using a fluorescent scanner under the same conditions as above, the fluorescence intensity (count number) of the test strip after the flow test was measured to obtain the spot intensity Isp, and the signal intensity S was calculated. The signal intensity S was divided by the noise value Nrms as follows to calculate the S / N ratio. As an example, scanning images of the test strip on which the antibodies according to Example 3 and Reference Example 1 are immobilized at an excitation wavelength of 488 nm are shown in FIG. 6. Scanning images of the test strip on which the antibodies according to Example 3 and Reference Example 1 are immobilized at an excitation wavelength of 532 nm are shown in FIG. 7.

[0153] The signal intensity S was calculated by subtracting the background average intensity Ib from the spot intensity Isp.

[0154] The spot intensity Isp was obtained by calculating the average value of the maximum intensity of the first spot and the maximum intensity of the second spot.

[0155] The background average intensity Ib was obtained by calculating the average value of the intensities of all pixels in the background part of the test strip after the flow test. The background part was a measurement area of ​​a 3 mm square area in the center, set at a position between the first spot part and the second spot part in the length direction of the membrane and 1 mm apart from both ends of the membrane in the width direction. The background average intensity Ib was obtained by calculating the average value of the intensities of all pixels in this measurement area.

[0156] The noise value Nrms was obtained by calculating the standard deviation of the intensities Ibi (i is the intensity of each pixel) of all pixels in the background area, as shown in the following formula (3). In other words, the noise value Nrms was determined as the root mean square of the deviation between the intensity Ibi of each pixel and the background average intensity Ib. Here, n represents the total number of pixels in the background area, and i represents an integer from 1 to n.

[0157]

number

[0158] Tables 3 to 6 show the preparation conditions and evaluation results of the analytical carriers in each example.

[0159] [Table 3]

[0160] [Table 4]

[0161] [Table 5]

[0162] [Table 6]

[0163] [Consider] Fig. 8 is a graph showing the relationship between the total organic acid concentration and the autofluorescence intensity. Fig. 9 is a graph showing the relationship between the total inorganic acid concentration and the autofluorescence intensity when irradiated with 488 nm excitation light. As shown in Fig. 8, it can be confirmed that there is a large correlation between the total organic acid concentration and the autofluorescence intensity. On the other hand, as shown in Fig. 9, it can be confirmed that there is a small correlation between the total inorganic acid concentration and the autofluorescence intensity when irradiated with 488 nm excitation light.

[0164] As shown in Table 4, the analytical support according to the embodiment has an organic acid concentration of the metal member of 150 mg / m 2 / 100 μm or less, and the analytical carrier according to the comparative example has an organic acid concentration of 150 mg / m 2 / 100μm. And, as shown in Table 4, the analytical carrier according to the embodiment had a relative value of autofluorescence compared to the aluminum standard reflector plate that was below 2.0. On the other hand, the analytical carrier according to the comparative example had a relative value of autofluorescence compared to the aluminum standard reflector plate that was above 2.0. And, as shown in Table 6, the analytical carrier according to the embodiment had a lower average background intensity and noise value than the analytical carrier according to the comparative example. Thus, it can be seen that the analytical carrier according to the embodiment has a suppressed autofluorescence signal derived from the components contained in the analytical carrier, and also has a suppressed signal emitted from the area other than the spot portion. Therefore, it can be seen that the analytical carrier according to the embodiment makes it easier to detect signals from the spot portion derived from the analyte with high sensitivity when performing an analysis in which excitation light is irradiated onto the analytical carrier and emitted light is detected.

[0165] In the analytical supports according to Comparative Examples 1 and 2, the electrolysis voltage for anodization was higher than that in the analytical supports according to Examples 1 to 3. This is thought to have resulted in the barrier layer of the anodized film being formed thicker, and a large amount of organic acid or organic acid-derived substances being taken in by the anodized film. 2 / 100μm, which is thought to be why autofluorescence increased.

[0166] The analytical support of Comparative Example 3 has a longer electrolysis time for anodization than the analytical support of Example 22. This is believed to have resulted in a thicker porous layer of the anodized film, and a large amount of organic acid or organic acid-derived substances being taken up in the anodized film. Furthermore, the analytical support of Comparative Example 4 has a shorter electrolysis time for anodization than the analytical support of Example 22, but a higher electrolysis voltage. This is believed to have resulted in a thicker barrier layer of the anodized film, and a large amount of organic acid or organic acid-derived substances being taken up in the anodized film. As a result, the organic acid concentration of the metal member was 150 mg / m 2 / 100μm, which is thought to be why autofluorescence increased.

[0167] In addition, from a comparison between Example 14, Example 16, Example 17, and Comparative Example 1, it was found that when inorganic acids such as phosphoric acid and boric acid were used in the electrolyte, and when adipic acid was used, the organic acid concentration was lower than when citric acid was used. In addition, from the results of Example 18 to Example 21, it was found that when inorganic acids such as sulfuric acid and phosphoric acid were used, the organic acid concentration was also lower.

[0168] Furthermore, when the analytical supports according to Examples 1 to 22 were irradiated with 488 nm excitation light, they all exhibited low autofluorescence and low noise values ​​Nrms, thereby demonstrating an excellent S / N ratio, compared with the nitrocellulose membrane filter of Reference Example 1. Furthermore, when the analytical supports according to Examples 1 to 16 and Example 22 were irradiated with 532 nm excitation light, they all exhibited low autofluorescence and low noise values ​​Nrms, thereby demonstrating an excellent S / N ratio, compared with the nitrocellulose membrane filter of Reference Example 1.

[0169] When irradiated with 532 nm excitation light, the analytical supports according to Examples 1 to 16 and 22 tended to have a higher S / N ratio than the analytical supports according to Examples 17 to 21. Here, it is considered that the influence of the components of the electrolyte remaining on the anodized film may cause an increase in noise value due to an increase in non-specific adsorption to the analytical support, or a decrease in signal intensity due to denaturation of the antibody or fluorescent substance adsorbed to the anodized film. It is considered that the analytical supports using the electrolyte containing organic acids such as citric acid, adipic acid, and oxalic acid in Examples 1 to 10, 16, and 22 had a high S / N ratio because the increase in noise value and the decrease in signal intensity, which may be caused by the influence of the components of the electrolyte remaining on the anodized film, were suppressed. It is considered that the analytical supports prepared using the electrolyte of ammonium dihydrogen phosphate in Examples 11 to 15 also had a high S / N ratio for the same reason.

[0170] Although the present embodiment has been described above with reference to examples and comparative examples, the present embodiment is not limited to these, and various modifications are possible within the scope of the gist of the present embodiment. [Explanation of symbols]

[0171] 1 Analytical Support 10 Metallic parts 20 Porous bodies 21 Aluminum particles 22 Skeleton 23 void 24 Outer shell

Claims

1. An analytical carrier comprising a metal member containing a porous body, The porous body includes a skeleton formed by an assembly of a plurality of aluminum particles and a plurality of voids surrounded by the skeleton, the skeleton has an outer shell including an anodized coating containing aluminum oxide on the surface of the aluminum particle, The porosity of the porous body is 30% by volume or more, The average particle size of the plurality of aluminum particles is 0.1 μm to 20 μm; The organic acid concentration of the metal member is 150 mg / m 2 An analytical carrier having a particle size of 100 μm or less.

2. 2. The analytical support according to claim 1, wherein the anodic oxide film is an organic acid anodic oxide film.

3. 3. The analytical support according to claim 1, wherein the anodized film is at least one selected from the group consisting of a citric acid anodized film, an adipic acid anodized film, and an oxalic acid anodized film.

4. 2. The analytical support according to claim 1, wherein the anodized film is at least one selected from the group consisting of a sulfuric acid anodized film, a phosphoric acid anodized film, and a boric acid anodized film.

5. 2. The analytical support according to claim 1, wherein the anodized film is at least one selected from the group consisting of a citric acid anodized film, an adipic acid anodized film, an oxalic acid anodized film, a phosphoric acid anodized film, and a boric acid anodized film.

6. The analytical support according to claim 1 or 2, wherein the anodic oxide film is a weak acid anodic oxide film.

7. 3. The analytical support according to claim 1, wherein the analytical support is used for performing a fluorescence analysis in which fluorescence emitted by irradiating the analytical support with excitation light is measured.

8. 8. The analytical carrier according to claim 7, wherein the wavelength of the irradiated excitation light is 250 nm to 650 nm, and the wavelength of the measured fluorescence is 350 nm to 700 nm.

9. A method for producing an analytical support having a metal member including a porous body, comprising: The porous body includes a skeleton formed by an assembly of a plurality of aluminum particles and a plurality of voids surrounded by the skeleton, the skeleton has an outer shell including an anodized coating containing aluminum oxide on the surface of the aluminum particle, The manufacturing method includes: a sintering step of sintering a plurality of aluminum metal particles to obtain a sintered body; an anodizing step of anodizing the sintered body to form the outer shell including the anodized coating on the surface of the aluminum metal particle, The average particle size of the plurality of aluminum metal particles is 0.1 μm to 20 μm; The packing ratio of the sintered body is 20% by volume to 70% by volume, The organic acid concentration of the metal member is 150 mg / m 2 A method for producing an analytical carrier, wherein the particle size is 100 μm or less.

10. The method for producing an analytical support according to claim 9 , wherein in the anodizing step, the sintered body is anodized using an electrolyte solution containing an organic acid.

11. The method for producing an analytical support according to claim 9 or 10, wherein in the anodizing step, the sintered body is anodized using an electrolyte containing at least one selected from the group consisting of citric acid, adipic acid, oxalic acid, and salts thereof.

12. 10. The method for producing an analytical support according to claim 9, wherein in the anodizing step, the sintered body is anodized using an electrolyte containing at least one selected from the group consisting of sulfuric acid, phosphoric acid, boric acid, and salts thereof.

13. 10. The method for producing an analytical support according to claim 9, wherein the anodization step is performed using an electrolyte solution containing at least one acid selected from the group consisting of citric acid, adipic acid, oxalic acid, phosphoric acid, and boric acid.

14. The method for producing an analytical support according to claim 9 , wherein the anodization step comprises anodizing using an electrolyte solution containing a weak acid.

15. An analytical method for analyzing an analyte supported on an analytical carrier, comprising the steps of: The analytical carrier is An analytical carrier comprising a metal member containing a porous body, The porous body includes a skeleton formed by an assembly of a plurality of aluminum particles and a plurality of voids surrounded by the skeleton, the skeleton has an outer shell including an anodized coating containing aluminum oxide on the surface of the aluminum particle, The porosity of the porous body is 30% by volume or more, The average particle size of the plurality of aluminum particles is 0.1 μm to 20 μm; The organic acid concentration of the metal member is 150 mg / m 2 / 100 μm or less, The analysis method includes: an irradiation step of irradiating the analytical support carrying the analyte with light having at least one wavelength included in the ultraviolet region to the infrared region; a detection step of detecting at least one type of light selected from the group consisting of reflected light, scattered light, transmitted light, fluorescence, and phosphorescence of the irradiated light; , an analytical method.

Citation Information

Patent Citations

  • Developing solvent for immuno-chromatography, measuring method and kit

    JP2003344406A

Cited By

  • Analysis carrier and method for producing analysis carrier

    WO2026211711A1

  • Analysis carrier and method for producing analysis carrier

    WO2026211716A1